Entrepreneurship and Household Income In Kotamobagu and Bolaang Mongondow - Kindangen, Paulus .; Tumiwa, Johan . (FEB Universitas Sam Ratulangi Manado, 2017)
The City of Kotamobagu and Regency of Bolaang Mongondow are two selected regions for this research. The respondents of this research are the head of households and/or housewives.The respondents were chosen purposively which are those of at least junior high school education. From 3 villages and 3 kelurahan (kelurahan is a village-level adminitrative region in a city), 60 households were chosen as respondent base. Thus, in average, 10 households were chosen from every village and kelurahan.The result of reseach shows that every independent variable – commitment and perseverance, initiative and action, and adaptive ability – does have positive and significant partial influence on household income in Kotamobagu and Bolaang Mongondow. It also shows that all the independent variables simultaneously influence household income positively and significantly.Keywords : household income, entrepreneurship, commitment and perseverance, initiative and action, and adaptive ability.